Identificación taxonómica de parásitos presentes en alevinos y juveniles de gamitana Colossoma macropomum provenientes de estanques del CIFAB, IIAP, Iquitos, Perú - Vargas de Pina, César Augusto (2021)
Colossoma macropomum popularly known as gamitana is one of the most important species of the Amazon ichthyofauna, highly demanded and with significant potential for Amazon fish farming and development. The “Instituto de Investigaciones de la Amazonía Peruana” (IIAP) incentives sustentable pisciculture through tecnological transference of native amazonian fish species, manily the gamitana. These fish are stocked in culture ponds of different owners, who in turn have to consider certain prophylactic measures to guarantee the adequate growth of the fish for subsequent commercialization in the markets of our city. In this sense, the present work aims to contribute to the knowledge of the species of parasites present in the gamitana, in order to obtain the necessary information for the proper management of this resource. In the present study, 60 specimens (30 fingerlings and 30 juveniles) of C. macropomum "gamitana" collected from culture ponds of the “Centro de Investigaciones Fernando Alcántara Bocanegra” (CIFAB) of the IIAP were analyzed. The samples were analyzed in the Laboratory of Parasitology and Aquaculture Health of the IIAP between August and Dezember 2020. From the analysis of the samples, four species of monogenoids were identified parasitizing the gills: Anacanthorus spatulathus, Notozothecium janauachaensis, Mymarothecium boegeri and M. iiapensis and one parasitizing the nostrils: Rhinoxenus piranhus; two species of Digenea: Austrodiplostomum compactum parasitizing the eyes and Clinostomum marginatum parasitizing the gills; two species of Copepoda: Amplexibranchius bryconis parasitizing the gills and Gamidactylus jaraquensis parasitizing the nostrils; a species of Isopoda: Anphira branchialis parasitizing the gills and a protozoan: Ichthiophthirius multifilis parasitizing the skin of fish. The diversity of ectoparasites recorded show that breed conditions of Amazonian fish favour the intraspecific contact between specimens of “gamitana” influencing in the transmission of parasites with direct life cycle as the ectoparasites.